Flame-Retardant Systems Based on Chitosan and Its Derivatives: State of the Art and Perspectives - Malucelli, Giulio (Molecules, 2020)
During the last decade, the utilization of chitin, and in par0ticular its deacetylated form, i.e., chitosan, for flame retardant purposes, has represented quite a novel and interesting application, very far from the established uses of this bio-sourced material. In this context, chitosan is a carbon source that can be successfully exploited, often in combination with intumescent products, in order to provide different polymer systems (namely, bulky materials, fabrics and foams) with high flame retardant (FR) features. Besides, this specific use of chitosan in flame retardance is well suited to a green and sustainable approach. This review aims to summarize the recent advances concerning the utilization of chitosan as a key component in the design of efficient flame retardant systems for different polymeric materials.